2012
DOI: 10.1681/asn.2012020166
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid CFHR3-1 Gene Causes Familial C3 Glomerulopathy

Abstract: Controlled activation of the complement system, a key component of innate immunity, enables destruction of pathogens with minimal damage to host tissue. Complement factor H (CFH), which inhibits complement activation, and five CFH-related proteins (CFHR1-5) compose a family of structurally related molecules. Combined deletion of CFHR3 and CFHR1 is common and confers a protective effect in IgA nephropathy. Here, we report an autosomal dominant complement-mediated GN associated with abnormal increases in copy nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 19 publications
1
100
0
Order By: Relevance
“…Five patients were previously described, comprising four patients with familial membranoproliferative GN (8) and one patient with persistent renal dysfunction and hypocomplementemia after streptococcal throat infection (13). No further familial cases were identified.…”
Section: Disease Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Five patients were previously described, comprising four patients with familial membranoproliferative GN (8) and one patient with persistent renal dysfunction and hypocomplementemia after streptococcal throat infection (13). No further familial cases were identified.…”
Section: Disease Incidencementioning
confidence: 99%
“…C3 glomerulopathy has been further divided into dense deposit disease (DDD) and C3 glomerulonephritis (C3GN) based on electron microscopy (EM) appearances. The underlying genetic defect has been identified in some hereditary forms of C3GN such as CFHR5 nephropathy (7,8). In contrast, most other reports of C3GN describe a diverse array of acquired and genetic abnormalities of complement regulation, in association with nonuniform histologic changes (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…Single SLE cases associated with different C3 mutations have been reported in the Japanese population [73,74]. Further, first described in patients of Cypriot origin, familial cases of C3G, associated with mutant CFHR proteins, have also been found in patients of other ethnicities [39,40,[75][76][77][78].…”
Section: The Genetic Background Of the Ap Abnormalities In Glomerularmentioning
confidence: 96%
“…The dysregulation of complement was present only on the certain surfaces, but (according to the authors) probably did not occur on the endothelium, explaining the C3G and not aHUS onset [39]. Malik et al [76] reported a unique hybrid CFHR3-1 gene, which caused a familial C3G. The authors speculate that this new gene interferes with C3 regulation by CFH and CFHR5, resulting in uncontrolled C3 activation and its accumulation in the kidney.…”
Section: Hereditary Ap Abnormalities In C3gmentioning
confidence: 98%
See 1 more Smart Citation